Anuria in a male calf - Aliye Sağkan Öztürk; Alparslan Coşkun; Şebnem Canikli; Mahmut Ok (Eurasian Journal of Veterinary Sciences)
In this study, a case of in 3.5 to 4 month old male calf suffering from anuria was evaluated clinical, hematological, biochemical, urinal ve ultrasonographical findings. Serum BUN, creatinine and K levels were increased. But Na and CI levels were decreased. Blood, protein and alot of crystals in urine was detected. In the ultrasonograph examination, sistitis and peritonitis were appeared.